Upaya Meningkatan Kompetensi Profesionalisme Guru melalui Pelatihan dan Pendampingan Penelitian Tindakan Kelas dan Publikasinya di SMP Negeri 2 Tengaran, Semarang - Prasetyo Listiaji; Novi Ratna Dewi; Erna Noor Savitri; Rizki Nor Amelia (Jurnal Dharma Indonesia, 2023)
This service activity was carried out in an effort to improve the professional competence of teachers at SMP N 2 Tengaran through training and assistance in Classroom Action Research (CAR) and its publication. A total of 40 teachers participated in this activity which was packaged in In Service Training (IST) and On Service Training (OST) for 32 Lesson Hours with three main stages namely preparation, implementation, and evaluation. Overall, efforts to improve the professionalism and competence of SMP N 2 Tengaran Semarang teachers through the implementation of community service went well. This is supported by the results of the evaluation questionnaire analysis, which concluded that the participants were very satisfied with the service activities carried out. In addition, the percentage of teacher completeness in preparing PTK proposals and preparing CAR articles is also in the good category.